LIVING SUNNAH TENTANG HIJRAH PARA ABITUREN NAHDHATUL WATHAN LOMBOK KE KOTABARU - Muhammad Zainudin Samima (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2016)
Prophet Muhammad, as the central figure in Islam, is an ideal model for Muslims so they compete to be as possible as similar to him in every ways. This deed can be called as living Sunnah. In the early days of Islam, he and his companions migrated (hijrah) from Makkah to Madinah to fulfill the order of Allah. Now, Muslims keep trying to imitate the Prophet’s deed in the context of social, culture, politics, economics and others. One of them is the community of Abituren Nahdhatul Wathan Lombok, they tried to imitate Prophet’s migration. They were out of hometown to migrate to Kotabaru with a mission to spread their organization’s propaganda. Therefore, this work tries to determine their understanding of the tradition of Prophet’s migration that initiate them to move to Kotabaru. This research is a field research, using three data collection techniques are observation, interviews and documentation. Then the nature of this study is qualitative, while the used approach is phenomenology to observe phenomena that occur in the community. In some conclusion, it can be said that the community of Abituren Nahdlatul Wathan Lombok understood the tradition of Prophet’s migration in the way of Allah and His messenger as a move to goodness that is blessed by Allah and His Messenger as appropriate guidance. In the modern era, their migration to Kotabaru reflexed the form of jihad and the strong intention to spread Islamic vision in the new community in Kotabaru.